2022
DOI: 10.1186/s12872-022-02504-0
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib related acute myocardial infarction with nonobstructive coronary arteries: a case report and literature review

Abstract: Background Myocardial Ischemia with No Obstructive Coronary Artery Disease (MINOCA) is a common cause of type 2 acute myocardial infarction (AMI) which requires careful differential diagnosis. Coronary artery spasm (CAS) syndrome is one etiology that can lead to MINOCA. Nilotinib, a targeted treatment for chronic myeloid leukemia (CML), has been reported to be related with increased risk of adverse vascular events. Case presentation A 67-year-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Of these, acute myocardial infarction, myocardial infarction, pericarditis, and cardiac tamponade exhibited mortality rates >10%. These AEs have been reported in several clinical studies [2528], and the present results are consistent with those clinical findings.…”
Section: Discussionsupporting
confidence: 94%
“…Of these, acute myocardial infarction, myocardial infarction, pericarditis, and cardiac tamponade exhibited mortality rates >10%. These AEs have been reported in several clinical studies [2528], and the present results are consistent with those clinical findings.…”
Section: Discussionsupporting
confidence: 94%
“…It is worth noting that the change in microcirculation is particularly pronounced in patients with existing vascular disease. Studies [ 11 ] on a similar medication, nilotinib, have also indicated that patients with pre-existing vascular disease are more likely to experience microcirculation disorders and amputations after treatment with nilotinib. Therefore, physicians should comprehensively evaluate the patient's vascular complications before making treatment decisions, to ensure more rational and safe choices.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the patient showed elevated levels of troponin I, myoglobin, and CK-MB. In addition, the patient's D-dimer and NT-proBNP levels were slightly elevated [ 70 ].…”
Section: Reviewmentioning
confidence: 99%